Secretory units of islets in transplantation index is a useful clinical marker to evaluate the efficacy of sitagliptin in treatment of type 2 diabetes mellitus - Kubota, Akira (Blackwell Publishing Ltd, 2011)
We carried out a retrospective analysis of 40 Japanese patients with type 2 diabetes mellitus who received sitagliptin. Glycated hemoglobin (HbA(1c)) and fasting plasma glucose were significantly decreased from 7.53 ± 0.65% and 155.2 ± 29.4 mg/dL at baseline to 6.80 ± 0.60% (P < 0.01) and 131.2 ± 22.3 mg/dL (P < 0.01) at week 20, respectively. β‐Cell function was evaluated by the secretory units of islets in transplantation (SUIT) index, which was significantly increased from 28.5 ± 14.0 at baseline to 38.6 ± 17.0 at week 20 (P < 0.01). Multivariate analysis was carried out between ΔHbA(1c) and several parameters (age, the duration of diabetes, body mass index, triglyceride [TG], C‐peptide [CPR], ΔCPR, HbA(1c) [baseline] and ΔSUIT), which showed HbA(1c) (baseline; β = 0.580, P < 0.001) and ΔSUIT (β = 0.308, P < 0.05) as significant independent determinants of ΔHbA(1c). These two variables explained 53% of the variance in HbA(1c) response. These results suggest that SUIT index can be a clinical marker for the efficacy of sitagliptin in treatment of diabetes mellitus. (J Diabetes Invest, doi: 10.1111/j.2040‐1124.2011.00109.x, 2011)